Marine flatworms (Platyhelminthes: Polycladida) found in empty barnacle shells, including a new species, from southern Mexican Pacific - Ramos-Sánchez, Mariela; Carrasco-Rodríguez, Dahani S.; García-Madrigal, María Del Socorro; Bastida-Zavala, J. Rolando (Zootaxa, 2021)
The association of some species of polyclads of the suborder Acotylea with barnacles has been recorded worldwide. In contrast, no species of the suborder Cotylea has been recorded present in these crustaceans. The aim of this work is to describe the species of polyclads found in the empty barnacle shells on the coasts of Oaxaca, southern Mexican Pacific. Thirty polyclad specimens in the barnacles’ empty shells were collected, corresponding to two species. A new species of acotylean, Stylochus mistus sp. nov., was found in Paraconcavus pacificus; and the cotylean Prosthiostomum cf. parvicelis in Megabalanus peninsularis. Both species of polyclads are considered to use the shells of Megabalanus and Paraconcavus as an occasional shelter site; however, it is not ruled out that these species feed on these barnacles, as polyclads normally prey on the communities they inhabit. This work records for the first time the presence of a cotylean polyclad in barnacles, as well as the first record of the polyclad genera Stylochus and Prosthiostomum from the southern Mexican Pacific.